THE FEASIBILITY OF MEASUREMENT OF (α,p) REACTION WITH RADIOACTIVE BEAM ²²Mg - NGUYEN , NGOC DUY; VUONG , HUU TAN; LE , HONG KHIEM; S. KUBONO (Nuclear Science and Technology, 2011)
This paper shows the feasibility of experiment of 22Mg(α,p)25Al reaction in environment of X-rays burst with temperature in GK, where the pure radioactive beams 22Mg approximately 0.29 1.24 MeV/u (lab) with temperature T9 = 1 3 (GK), are created by primary reaction 3He(20Ne, 22Mg)n reaction and online filtered by CRIB. The projectile 22Mg bombards to secondary target filled with Helium gas. The experiment is designed based on inverse kinetics by using thick target method to scan resonance states above alpha threshold. We can measure the cross section, and evaluate the rate of 22Mg(α,p)25Al reaction. They are useful for explanation of anomaly in astronomy and for study of resonance states of 26Si.